Soil Application of Almond Residue Biomass Following Black Soldier Fly Larvae Cultivation - Axelrod, Robert; Palma Miner, Lydia; VanderGheynst, Jean S.; Simmons, Christopher W.; Fernandez-Bayo, Jesús D. (Frontiers in Sustainable Food Systems, 2021)
Insect farming has the potential to transform abundant residual biomass into feed that is compatible with non-ruminant animal production systems. However, insect cultivation generates its own by-products. There is a need to find valuable and sustainable applications for this material to enable commercial-scale insect farming. Soil application of by-products, which may be either basic broadcasting incorporation or part of a sustainable soil borne pest management practice, such as biosolarization, could offer an agricultural outlet. The objective of this study was to assess the potential of applying black soldier fly larvae (BSFL)-digested substrate as soil amendment for soil biosolarization and evaluate its impact on soil health. Sandy loam (SL) and sandy clay loam (CL) soils amended with BSFL-digested almond processing residues, i.e., spent pollinator hulls (SPH), at 2% dry weight (dw) were incubated under aerobic and anaerobic conditions for 15 days under a daily fluctuating temperature-interval (30–50°C). The microbial respiration, pH, electrical conductivity, volatile fatty acids, macronutrients, and germination index using radish seeds (Raphanus sativus L.) were quantified to assess the soil health after amendment application. Incubation showed a statistically significant (p < 0.05) increase in electrical conductivity related to amendment addition and a decrease potentially linked to microbiological activity, i.e., sequestering of ions. Under aerobic conditions, SPH addition increased the CO2-accumulation by a factor of 5–6 compared to the non-amended soils in SL and CL, respectively. This increase further suggests a higher microbiological activity and that SPH behaves like a partially stabilized organic material. Under anaerobic conditions, CO2-development remained unchanged. BSFL-digested residues significantly increased the carbon, nitrogen, C/N, phosphate, ammonium, and potassium in the two soil types, replenishing soils with essential macronutrients. However, greenhouse trials with lettuce seeds (Lactuca sativa) lasting 14 days resulted in a decrease of the biomass by 44.6 ± 35.4 and 35.2 ± 25.3% for SL and CL, respectively, compared to their respective non-amended soil samples. This reduction of the biomass resulted from residual phytotoxic compounds, indicating that BSFL-digested SPH have the potential to be used for biosolarization and as soil amendments, depending on the concentration and mitigation strategies. Application and environmental conditions must be carefully selected to minimize the persistence of soil phytotoxicity.